PREFERENSI MAHASISWA TERHADAP PENCAHAYAAN BUATAN IDEAL UNTUK RUANGAN KELAS STUDIO GAMBAR - Leonardo . (Serat Rupa: Journal of Design, 2020)
Drawing studio is essential for design students because it is used intensively and in a prolonged time. Lighting for drawing studio can support students drawing performance when installed properly. Hence, students’ preference for ideal lighting for drawing studios is aimed at this study. Conjoint analysis is used to look into students’ preferences through a set of designed profiles. Eight profiles for lighting studios are designed to consist of seven attributes with two levels each, resulting in rendered images by computer and then are exposed to 145 active students of design interior from the ongoing semester. The finding shows three main attributes, lighting distribution (27.3%), overall lighting intensity (18.2%), and desk-level lighting intensity (13.7%) are preferred the most consecutively. This study concludes those three main attributes as the most influential for lighting studio to support students drawing performance, while the rest are considered added value when the main three attributes are already fulfilled.